2019
DOI: 10.1103/physreva.100.023830
|View full text |Cite
|
Sign up to set email alerts
|

Control of a quantum emitter's bandwidth by managing its reactive power

Abstract: Reactive power plays a crucial role in the design of small antenna systems, but its impact on the bandwidth of quantum emitters is typically disregarded. Here, we theoretically demonstrate that there is an intermediate domain between the usual weak and strong coupling regimes where the bandwidth of a quantum emitter is directly related to the dispersion properties of the reactive power. This result emphasizes that reactive power must be understood as an additional degree of freedom in engineering the bandwidth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…This contribution reflects the absorptive part of the mode dissipation. Furthermore, we note that the expression forS in μη,α (ω) for a single mode is similar to the classical absorptive part connected to the Poynting theorem [58], and we will henceforth call it the nonradiative partS in μη,α (ω) =S nrad μη,α (ω). We are left with the contribution connected toS out μη (ω) = lim α→0 lim λ→∞S out μη,αλ (ω):…”
Section: Commutation Relation Of the Qnm Operators In The Dielectrmentioning
confidence: 99%
“…This contribution reflects the absorptive part of the mode dissipation. Furthermore, we note that the expression forS in μη,α (ω) for a single mode is similar to the classical absorptive part connected to the Poynting theorem [58], and we will henceforth call it the nonradiative partS in μη,α (ω) =S nrad μη,α (ω). We are left with the contribution connected toS out μη (ω) = lim α→0 lim λ→∞S out μη,αλ (ω):…”
Section: Commutation Relation Of the Qnm Operators In The Dielectrmentioning
confidence: 99%
“…It must be noticed that even in these cases, the interaction between the emitter and the reservoir modes can be quite strong, and the induced frequency shifts can be large enough to significantly affect the bandwidth of the emitter radiation. [ 45 ] One can even seek to manipulate the emission spectrum and, at the same time, greatly enhance the emission rate, as is the case for the recently suggested hybrid antenna‐cavity scheme. [ 44,46 ]…”
Section: Quantum Antennasmentioning
confidence: 99%
“…In particular, it has recently been shown that a system with one upper and three degenerate lower levels can act as an isotropic unpolarized coherent single‐photon emitter. [ 45 ]…”
Section: Quantum Antennasmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. 52) as an integral over the (time-averaged) Poynting vector, which in terms of the classical fields yields S Poynting =0.5Re(E(ω) × H * (ω)). The S rad (ω) thus has a clear interpretation: it is the normalized QNM power flow outside the antenna and it appears naturally in our formalism.…”
Section: B Quantized Quasinormal Mode Theorymentioning
confidence: 99%